Determine the Complications of Transradial Approach in Patients Undergoing Percutaneous Coronary Interventions (Medical Forum Monthly, 2020)
Objective: To examine the prevalence of complications related with transradial approach in patients undergoing elective percutaneous coronary interventions.Study Design: Cross-sectional/observationalPlace and Duration of study: This study was conducted at the Department of Cardiology, Bolan Medical Complex Hospital Quetta from January 2019 to December 2019.Materials and Methods: One hundred and ten patients of both genders with ages 20 to 75 years undergoing percutaneous coronary interventions were included. Patients detailed demographic including age, sex, body mass index and com-morbidities were recorded after taking informed written consent from all the patients. All the patients were received transradial approach and periprocedural complications were examined.Results: There were 82 (74.55%) males while remaining 28 (25.45%) were females with mean age 57.85±8.54 years. Mean BMI was 27.12±3.45. Hypertension was the most common morbidity found in 50% patients followed by diabetes mellitus and smoking. Minor bleeding was the commonest complication found in 25 (22.73%) patients followed by radial artery occlusion, excessive bleeding, radial nerve injury and hematoma in 7 (6.36%), 6 (5.45%), 4 (3.64%) and 2 (1.82%) patients respectively.Conclusion: Transradial approach for coronary interventions is safe and effective with fewer rates of complications.